Evaluating the Natrium Iodide Symporter Expressions in Thyroid Tumors - Elliyanti, Aisyah; Rustam, Rony; Tofrizal, Tofrizal; Yenita, Yenita; Susanto, Yayi D. Billianti (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Decreased Natrium iodide symporter (NIS) expression levels or diminished NIS targeting thyroid cancer cells’ plasma membrane leads to radioiodine-refractory disease. AIM: The aim of this study was to analyze the NIS expression in thyroid tumors. MATERIALS AND METHODS: The samples were thyroid tissues of patients who underwent surgery for a thyroid tumor. The tissues were processed for NIS protein expressions by immunohistochemistry (IHC) and Western blot (WB). Graves’ disease samples were used as positive controls. The samples were incubated without the primary antibody, and they were used as negative controls for IHC examination. Na+/K+ ATPase was a plasma membrane protein marker in the WB procedure. RESULTS: Twenty-nine samples were assessed for NIS protein. All of them showed the expression in the cytoplasm with intensity 1+ to 3+ with Allred score 3-8. Fourteen out of 29 cases (48.2%) showed NIS cytoplasm staining intensity ≥2+ consist of 10 papillary thyroid cancer (PTC), three follicular thyroid cancer, and one adenoma. Membrane staining was found in 2 samples of PTC (6.9%). Six samples (adenoma 1 sample, PTC 5 samples) showed NIS expression at membrane very weak (1+); they were considered as negative. NIS protein has several bands of ~ 80 kDa, ~ 62 kDa, and ~ 49 kDa. CONCLUSION: NIS expression in thyroid cancer mostly expresses in the cytoplasm instead of the membrane. NIS will play a functional role in the membrane to bring iodine across the membrane against the concentration. It can be the main reason for the lack of response of radioiodine in some differentiated thyroid cancers.